The geography of ecological niche evolution in mammals - Mazel, Florent (Curr Biol, 2017)
Convergent adaptive evolution of species’ ecological niches — i.e. the appearance of similar niches in independent lineages—is the result of natural selection acting on niche-related species traits (‘traits’ hereafter) and contrasts with neutral evolution [1–4]. While trait convergences are recognized as being of importance at the species scale, we still know little about the impact of species convergence on the overall trait and niche structure of entire biotas at large spatial scales [5]. Here, we map the convergent evolution of four traits (diet, body-mass, activity cycle and foraging strata) for mammal species and assemblages (defined at 200x200km resolution) at a global scale. Using data on the geographic distributions, traits, and phylogenetic relationships of species and by comparing observed patterns of trait β-diversity to evolutionary neutral expectations, we show that trait convergence is not restricted to particular lineages, but scales up to entire assemblages (i.e. whole species communities). We find region-wide biota convergence in traits between regions with similar climates, particularly between Australia and other continents. Pairs of assemblages that show trait divergence often involve arctic regions where rapid evolutionary changes occurred in response to extreme climatic constraints. By integrating both macro-ecological and macro-evolutionary approaches into a single framework, our study quantifies the crucial role of evolutionary processes such as natural selection in the spatial distribution and structure of large-scale species assemblages.